Usability vs. Security: The Everlasting Trade-Off in the Context of Apple iOS Mobile Hotspots - Kurtz, Andreas; Freiling, Felix; Metz, Daniel (2013)
Passwords have to be secure and usable at the same time, a trade-off that is long known. There are many approaches to avoid this trade-off, e.g., to advice users on generating strong passwords and to reject user passwords that are weak. The same usability/security trade-off arises in scenarios where passwords are generated by machines but exchanged by humans, as is the case in pre-shared key (PSK) authentication. We investigate this trade-off by analyzing the PSK authentication method used by Apple iOS to set up a secure WPA2 connection when using an iPhone as a Wi-Fi mobile hotspot. We show that Apple iOS generates weak default passwords which makes the mobile hotspot feature of Apple iOS susceptible to brute force attacks on the WPA2 handshake. More precisely, we observed that the generation of default passwords is based on a word list, of which only 1.842 entries are taken into consideration. In addition, the process of selecting words from that word list is not random at all, resulting in a skewed frequency distribution and the possibility to compromise a hotspot connection in less than 50 seconds. Spot tests show that other mobile platforms are also affected by similar problems. We conclude that more care should be taken to create secure passwords even in PSK scenarios <br
UnivIS-Import:2016-06-30:Pub.2013.tech.IMMD.lehrst.usabil